PENGARUH POLA ASUH OTORITER TERHADAP MOTIVASI BELAJAR MURID KELAS X SMK NEGERI 2 LUBUKLINGGAU - Arwani Arwani; Bramana Nanditya Putra; Dina Ervina (MUHAFADZAH: Jurnal Ilmiah Bimbingan dan Konseling Islam, 2026)
Authoritarian parenting refers to a parenting style that emphasizes a child's complete obedience to parental commands and wishes. Learning motivation can be defined as the overall psychological strength that emerges from within a student and drives learning activities. Research aim to know influence of authoritarian parenting on learning motivation in 10th-grade Hospitality students at SMK Negeri 2 Lubuklinggau. This research used a quantitative survey approach with a population of 102 10th-grade Hospitality students at SMK Negeri 2 Lubuklinggau and a sample of 37 students using a purposive sampling method. Data collection used a Likert scale of 1-4. The data analysis technique used SPSS version 26. Based on the r result or person correlation of 0.259 with a significance value (Sig. 2-tailed) of 0.122 indicates a weak correlation interval. The calculated F value of 2.511 and a significance value of 0.122 because the significance value is greater than 0.05 (0.122 > 0.05), the relationship is not statistically significant. This shows that authoritarian parenting does not significantly influence student learning motivation. Thus, H0 is accepted and Ha is rejected, which means authoritarian parenting is not the main predictor in explaining changes in the level of learning motivation. The coefficient of determination (R Square) value obtained of 0.067 indicates that authoritarian parenting only contributes 6.7% to student learning motivation. The remaining 93.3% is influenced by other factors not examined in this study.